Language Attitude in Startup Company PT Inovasi Edukasi Karya Anak Negeri: A Sociolinguistics Study - Sapta Eky Abdillah; Ervina C M Simatupang (Jurnal Sinestesia, 2023)
This research was intended to analyze the language attitude of employees in the startup company PT. Inovasi Edukasi Karya Anak Negeri, based on Ronald Wardhaugh and Janet M. Fuller’s theory about sociolinguistics (2015). The method of this research is a quantitative questionnaire, with the respondents being 36 employees. The research is focused on finding the cause of multilingualism, and the language attitude of employees. The employee is Sundanese, Javanese, Batak Karo, Banjar, Batak, and Tionghoa. The result of this research is 12 employees are bilingual (33.3%), 24 employees are multilingual (66.6%), and does not find monolingual employees. The biggest factors of multilingualism are social, family, and education. Widely used languages are Indonesian, English, Sundanese, and Javanese. As a result of language attitude, 100% feel proud of their ethnic language. All employees want to sustain and maintain the language. Then 100% aware of the norms of the language.